Slum Structuring Strategy With Collective Housing Concept - Puspita, Dinda; Fadhly, Noer; Zukhrina Oktaviani, Cut (Publisher Cv. Inara, 2025)
Telaga Tujuh Village, located in West Langsa Sub-district, Langsa City, on the eastern tip of Aceh, has a very high population density. In addition, 373 housing units in the village do not meet the technical criteria set out in the Minister of Public Works and Housing Regulation No.02/PRT/M/2016, and the city has limited access to critical infrastructure. Based on seven criteria, including building regularity, neighborhood road network, neighborhood drainage, drinking water needs, wastewater management system, waste management facilities and infrastructure, and fire protection facilities, Telaga Tujuh Village is classified as a severe slum, with an average slum rate of 100%. Discovering the structural needs of the slum environment in Telaga Tujuh Village and creating a structural design is the objective of this study. Five indicators - on-site upgrading, on-site relocation, on-site redevelopment, land sharing, and relocation - were used in the communal housing methodology in this study. On-site redevelopment was chosen as the minimum solution after the five indicators were selected using the Analytical Hierarchy Process (AHP) method. After on-site redevelopment, the settlement pattern in this area is in the form of an iron grid, with main centers-the construction of places of worship, village halls, auxiliary health centers (pustu), and village offices that function as government and community service centers-and supporting centers-education and neighborhoods-by providing public open spaces.